2014
DOI: 10.1111/jnc.12940
|View full text |Cite
|
Sign up to set email alerts
|

Larvae of the small white butterfly, Pieris rapae, express a novel serotonin receptor

Abstract: The biogenic amine serotonin (5-hydroxytryptamine, 5-HT) is a neurotransmitter in vertebrates and invertebrates. It acts in regulation and modulation of many physiological and behavioral processes through G-protein-coupled receptors. Five 5-HT receptor subtypes have been reported in Drosophila that share high similarity with mammalian 5-HT 1A , 5-HT 1B , 5-HT 2A , 5-HT 2B , and 5-HT 7 receptors. We isolated a cDNA (Pr5-HT 8 ) from larval Pieris rapae, which shares relatively low similarity to the known 5-HT re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…This receptor also occurs in the parasitic nematode Haemonchus contortus and is predicted to be present in several additional nematodes (Komuniecki et al, 2012;Beech et al, 2013), but it has not been reported in other invertebrate clades. In the butterfly P. rapae, a novel receptor has been described by Qi et al (2014) that is proposed to belong to a new family of receptors designated 5-HT 8 . 5-HT activation of this receptor in HEK293 cells induced an increase in Ca 2+ , but the sequence and pharmacology do not resemble 5-HT 2 or other insect 5-HT receptors.…”
Section: Rnai Knockdownmentioning
confidence: 99%
“…This receptor also occurs in the parasitic nematode Haemonchus contortus and is predicted to be present in several additional nematodes (Komuniecki et al, 2012;Beech et al, 2013), but it has not been reported in other invertebrate clades. In the butterfly P. rapae, a novel receptor has been described by Qi et al (2014) that is proposed to belong to a new family of receptors designated 5-HT 8 . 5-HT activation of this receptor in HEK293 cells induced an increase in Ca 2+ , but the sequence and pharmacology do not resemble 5-HT 2 or other insect 5-HT receptors.…”
Section: Rnai Knockdownmentioning
confidence: 99%
“…Furthermore, these G protein-coupled 5-HT receptors are mainly classified in three groups: (1) 5-HT1 and 5-HT5 receptors that couple preferentially to Gi proteins and inhibit cAMP synthesis, (2) 5-HT2 receptors that activate Gq proteins, which mediate the hydrolysis of inositol phosphates and cause a subsequent increase in cytosolic Ca 2+ , and (3) 5-HT4, 5-HT6, and 5-HT7 receptors that couple to Gs proteins and promote cAMP formation1819. Additionally, an extra novel serotonin receptor (named Pr5-HT8) has been identified from larval Pieris rapae and, and represents the first recognized member of a novel 5-HT receptor class with a unique pharmacological profile20. In marine invertebrates or dormancy animals, only several serotonin receptors have been identified from the barnacle, Balanus amphitrite Darwin21 and the marine mollusc Aplysia 2223, however, the 5-HT receptors and their physiological functions in marine invertebrates still remain largely unknown.…”
mentioning
confidence: 99%
“…An additional receptor, MOD-1, a serotonin-gated ion channel, was found in C. elegans and exhibited similarities to the mammalian 5-HT3 receptor, but with differences in function ( 76 ). Qi et al ( 77 ) reported a novel receptor in the butterfly Pieris rapae , that was classified into a new family of receptors designated as 5-HT8. As in vertebrates, serotonin activates different downstream signaling pathways in order to control levels of second messengers, specifically adenylate cyclase activity and cAMP production (inhibited by Gi-coupled 5-HT1-like receptors, but stimulated by Gs-coupled 5-HT7-like receptors) or phospholipase C, and subsequently increases Ca 2+ (stimulated by Gq-coupled 5-HT2-like receptors) ( 75 ), to exert both inhibitory and excitatory effects.…”
Section: Serotoninmentioning
confidence: 99%